520 Summative process evaluation of a driver licensing support program in remote aboriginal communities. (1st September 2016) - Cullen, Patricia; Chevalier, Anna; Byrne, Jake; Hunter, Kate; Gadsden, Tom; Ivers, Rebecca
Abstract : Background: Aboriginal people in the Northern Territory (NT) have low rates of driver licensing, which is likely to contribute to high rates of transport-related injury, high rates of incarceration for regulatory driving offences and reduced access to employment, education and essential health services. The DriveSafe NT Remote program was implemented by the NT Government to increase driver licensing in remote communities. This evaluation reviews the program delivery, acceptability, implementation challenges and licensing outcomes. Methods: A mixed-methods approach was used, incorporating program observation and key informant perspectives. Program data (collected April 2012 to June 2014) and de-identified licensing data from the NT Motor Vehicle Registry were analysed for trends in service delivery and licensing rates pre and post-program. Results: Stakeholders reported that the program is meeting the needs of underserviced remote communities, and regarded the program as highly engaging and acceptable. There was a greater increase in new licences at intervention sites (Learner 24% and Open licence 18%) compared with other remote areas (Learner licence 13% and Open licence 8%). There appeared to be a dose response relationship with greater licence outcomes at communities that received higher levels of program delivery. Conclusions: DriveSafe NT Remote is a Government delivered program that is acceptable to Aboriginal clients in remote NT communities, and is increasing driver licensing rates in these settings. The flexible delivery and culturally responsive approach should allow continuation of positive licensing outcomes.